EDUKASI 1OOO HPK SEBAGAI UPAYA PENCEGAHAN DAN PENURUNAN STUNTING DI DESA PUKDALE KECAMATAN KUPANG TIMUR - Sormin, Roslin E.M; Mangngi, Atalia Pili; Atok, Yosefa S.; Nuhan, Maria V.; Manek, Brigita D.; Ria, Matilda Bupu; Ilma, Nabilah N.; Duka, Maria M. T.; Gusman, Avelina P.; Palalangan, Damita; Alang, Ermi L.; Satiti, Diah A.D; Fernandez, Ninick C.; Babys , Deviserlina; Murti, Ni Putu I.D.P; Fangi, Windy F.; Babis , Sonida S. D. (Jurnal Abdi Insani, 2024)
Stunting is a chronic nutritional problem that causes stunted physical growth, while development is the process of changing a person's behavior and mental state including emotional, social, abilities and skills. Efforts to prevent STUNTING can be made by educating about the importance of the first 1000 days of life. To provide education and increase public understanding about the importance of the first 1000 days of life as an effort to prevent STUNTING. This activity was carried out at the Pukdale village office with the target being pregnant women, mothers with babies, mothers of toddlers and couples of childbearing age and the general public in Pukdale village. Counseling or education to the community by involving stakeholders as supporters of creating a healthy generation. This activity was attended by a target group of 50 people consisting of pregnant women, mothers with babies and toddlers and also the general public. All participants were enthusiastically involved and interacted with the resource person through discussion and question and answer sessions. This activity had a very good impact on all participants because there was an increase in knowledge based on the results of the questionnaire examination.